Fahrplanbasiertes Energiemanagement in Smart Grids - Hirsch, Christian (KIT Scientific Publishing, 2017)
The increase in decentralized, volatile electricity generation as result of the German energy system transformation causes congestions in electricity grids. IT networking and coordination of producers and consumers in smart grids promises a solution to these problems. In this context, this work presents an energy management approach that approximates specified, aggregated power profiles. The approach uses power forecasts and flexibilities and takes network restrictions into account.